Nevus Sebaceous of Jadassohn Mimicking a Pilonidal Sinus of Forehead: A Rare Case Presentation - Parindita Sarmah; Prasad Deshmukh; Sagar Gaurkar (Journal of Clinical and Diagnostic Research)
Nevus Sebaceous of Jadassohan (NSJ) is a hamartoma that presents as a cutaneous lesion, which can be considered an overgrowth of sebaceous glands, hair follicles, and other epidermal structures. Although it is usually a benign condition, the lesion is capable of producing secondary neoplasms, both benign and infrequently, malignant. This case report discusses a 21-year-old male patient who presented with a lesion on the forehead, manifesting as a pilonidal sinus due to the presence of a tuft of hair at the end of the sinus tract following childhood trauma. The presence of a sinus tract with hair growth in the glabellar region is a rare and diagnostically challenging presentation of NSJ. This case highlights the complexities of managing such chronic wounds and the potential complications arising from trauma.